PENGEMBANGAN E-FLASHCARD MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Nurhaliza, Siti Nurhaliza; Sukirno; Inge Ayudia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research found that the use of interactive digital learning media in Pancasila Education learning is still not varied, the role of students is still as recipients of information and learning is still teacher-centered so that student involvement in the learning process is not optimal. This study aims to determine the feasibility of e-flashcard learning media in Pancasila Education learning on the Pancasila in My Life material. This research was conducted at Gampong Teungoh Elementary School. The subject of this research is a type of research and development, namely Research and Development (R&D). The research design used in this study consists of 5 stages, namely the ADDIE model (analysis, design, development, implementation, and evaluation). The data collection technique used a Likert scale. The data collection instrument used a validation questionnaire from material experts, media experts, language experts, teacher response questionnaires, and student response questionnaires. The data analysis techniques used in this study were qualitative and quantitative analysis techniques. The results of the research obtained from the e-flashcard learning media obtained an assessment of 93.33% from material experts with the category "very valid", 98.57% from media experts with the category "very valid", 92.72% from language experts with the category "very valid". The level of practicality in using the e-flashcard learning media received an assessment from the teacher response questionnaire of 87.5% with the category "very practical", 87% from student response questionnaires with the category "very practical". So the e-flashcard media for the Pancasila in My Life material is suitable for use as a learning medium because it meets the valid and practical criteria. Therefore, this media can be used by teachers as an alternative learning media for Pancasila Education and can be further developed with more interactive features in subsequent research.